Carrying Capacity for Ruminant Based on Plantation Byproducts and Potency of Enteric Methane Emission - Gresy Eva Tresia; W Puastuti; I Inounu (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2021)
Feed is one of the main pillars that need to be considered in optimizing production parameters in order to develop an efficient livestock business. Two aspects that need to be considered in order to make agricultural byproducts as a source of feed; those are the availability of raw materials for animal rations with high economic value and the function to  reduce environmental pollution. Methane emissions are not only related to environmental problems, but also reflect the loss of some energy from livestock so that it cannot be used for the production process. The purpose of this paper is to review and estimate the carrying capacity for ruminant based on plantation by-products based feed and potential enteric methane emissions. The availability of feed from agricultural byproducts in Indonesia is estimated at 69.6 million tonnes of dry matter (DM), 34.8 million of total digestible nutrient (TDN), and 5 million tonnes of crude protein (CP)/year so it is estimated that it can accommodate 62.4 million livestock unit (LU) based on the DM availability or 39.1 million LU based on TDN availability or 51.6 million LU based on CP availability. From these calculations, it was found that the carrying capacity for ruminant in Indonesia could still be increased much greater than the current livestock population, namely 21.7-45 million livestock units if all byproducts are used entirely as components in rations. There are two groups of feed originating from plantation byproducts based on the potential for methane emissions produced, namely low (65-73 g CH4 / kg of material) and high (83-103 g CH4 / kg of material). Utilization of plantation byproducts as ruminant feed is expected to overcome the shortage of forage, especially during dry season. Utilization of these byproducts which in line with efforts to reduce methane emissions would enhance the development of livestock populations in friendly environment.